2002
DOI: 10.1590/s0066-782x2002000100006
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of electrocardiographic criteria for determining left ventricular hypertrophy

Abstract: The Cornell index had greater sensitivity in women, and the Sokolow-Lyon-Rappaport index was more sensitive in men. When applied to men at the same voltage amplitude as that of women, the Cornell index had an increase in sensitivity similar to that of the Sokolow-Lyon-Rappaport index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
4
8
1
1
Order By: Relevance
“…The analysis of the area under the ROC curve 20,21 allows the assessment of the performance of one or more tests under a large margin of possible cut-off points, thus permitting the identification and comparison of the differences of performances between methods, regardless of empirically defined criteria. By using this methodology, the present study confirms the superiority of the Cornell criterion over the SLR criterion, as shown in Figure 2, thus corroborating the findings of other studies 9,28,32 . For a more clear analysis of the performance of the criteria studied, sensitivities were compared in relation to a fixed specificity level of 95% which, in addition to being the most widely used in the literature 22,23 , also reaches the clinical purposes of the method (Table 3).…”
Section: Fig 3 -Sokolow-lyon-rappaport (Slr) and Cornell Indexes Obtsupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of the area under the ROC curve 20,21 allows the assessment of the performance of one or more tests under a large margin of possible cut-off points, thus permitting the identification and comparison of the differences of performances between methods, regardless of empirically defined criteria. By using this methodology, the present study confirms the superiority of the Cornell criterion over the SLR criterion, as shown in Figure 2, thus corroborating the findings of other studies 9,28,32 . For a more clear analysis of the performance of the criteria studied, sensitivities were compared in relation to a fixed specificity level of 95% which, in addition to being the most widely used in the literature 22,23 , also reaches the clinical purposes of the method (Table 3).…”
Section: Fig 3 -Sokolow-lyon-rappaport (Slr) and Cornell Indexes Obtsupporting
confidence: 91%
“…Considering that ECG is still the main tool for the diagnosis of LVH in most health services, especially in those linked to the public network focused on primary care, the objective of this study was to determine values of Sokolow-Lyon-Rappaport 8,9 and Cornell 10 voltage criteria in a general population sample included in an epidemiological study conducted in the city of Vitória, ES, (WHO-MONICA Project/Vitória) 11,12 with the purpose of determining the prevalence and severity of cardiovascular risk factors. The study enabled the definition of new cut-off points for LVH on ECG, using ECHO findings (M-mode guided by the two-dimensional mode, using images interventricular septal and LV posterior wall thickness were measured at end-diastole, which was defined by the beginning of the QRS complex as monitored by simultaneous electrocardiography.…”
Section: Introductionmentioning
confidence: 99%
“…ECG signals were analyzed for left ventricular hypertrophy and assessed by the voltage-duration product, as previously described (13). The voltage-duration product was considered to be abnormal if greater than 2440 mV/s, defining left ventricular hypertrophy.…”
Section: -Lead Surface Ecg Acquisitionmentioning
confidence: 99%
“…In the same way that modern electrocardiography (ECG) has clearly benefited heart patients [16][17][18][19][20][21], uterine EMG which, similarly, amounts to the acquisition of electrical signals taken non-invasively from surface electrodes, would likely benefit obstetric patients when adopted by physicians, and when utilized as an everyday tool in the antenatal and labor wards and clinics. Like the function of the ECG for cardiac monitoring, uterine EMG can be used to monitor uterine electrical recordings in normal pregnancies in order to diagnose or even predict abnormal conditions such as preterm labor, insufficient labor progress, or dystocia [22].…”
Section: Monitoring During Pregnancy (And Diagnosis Of Labor)mentioning
confidence: 99%